The Geographical Spread of The Corona Virus and The Economic Implications in Districts of Makka City - Jabri, Jalila Ali Hamad; Ghamry, Sami Salah (Journal of Humanities & Social Sciences, 2024)
This study aims to identify the Relation between the geographical spread of the Corona virus and its economic repercussions in the neighborhoods of the Holy City of Makka. The researcher discussed: the environment and origins of the Corona disease, the geographical spread of the Corona virus, and the economic repercussions and its repercussions on the rest of the aspects of life in the neighborhoods of the Holy City of Makka as a result of the spread of this virus. The main results of the current study including that Corona pandemic has health, psychological, social and economic repercussions. By studying the geographical spread pattern of the virus, it was found that it would determine the varying degrees of damage, especially in the neighborhoods of the Makkah region. Stores, commercial centers, and other places that could constitute a source of danger for the spread of the Corona virus (Covid-19), and instructions have been issued to take precautionary measures to limit the spread of the virus and its impact on the economic situation of the Makkah region, which had a significant impact in not increasing the spread of the virus. The Kingdom has taken all the precautionary measures that have been praised by international organizations to prevent the transmission of the Corona virus, with the necessity of respecting the security distance of at least one meter between two people, and applying these precautions compulsorily to all activities not concerned with the closure, and public administrations taking all necessary arrangements to implement it and enforcing its respect by all means, including This includes the use of public force. The study recommended the need for health and economic authorities in the Kingdom to join forces with their counterparts in countries around the world and international organizations to reach effective treatment that eliminates the virus and its repercussions.